Method for evaluating damage tolerance of composite material L-shaped plate with layering defect

By constructing and optimizing the numerical model of L-type laminated plates, analyzing the impact of layered defect locations on load capacity, the high cost and low efficiency problems of preparing a large number of defect samples in the prior art for load testing are solved, and a systematic study of the bearing capacity of L-type composite laminated plates is realized.

CN119785936AActive Publication Date: 2025-04-08WUHAN UNIV OF TECH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411851614.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-08
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The prior art is difficult to systematically study the impact of stratified defects on load-bearing capacity at any position in the L-type composite laminate, and it is necessary to prepare a large number of defect samples for load testing, which is costly and inefficient.

Method used

By preparing defect-free L-type laminated plate samples for loading tests, recording the stress distribution cloud map and the crack starting position at critical moments, building a numerical model of the L-type laminated plate containing cohesive units, and correcting them based on experimental data, designing prefabricated stratified defects, optimizing the numerical model to obtain an interlayer damage model that is sensitive to defect positions, and analyzing the impact of stratified defect positions on load carrying capacity and failure mode.

Benefits of technology

It is possible to comprehensively study the impact of layered defect location on the bearing capacity of L-type laminate composite materials without the need to prepare a large number of defect samples, reducing costs and improving load testing efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119785936A_ABST
    Figure CN119785936A_ABST
Patent Text Reader

Abstract

The invention discloses a damage tolerance evaluation method for a composite material L-shaped plate containing a layering defect, and belongs to the technical field of a comprehensive evaluation system of an experimental data correction numerical model, and the method comprises the following steps: preparing a defect-free L-shaped laminated plate sample, carrying out a loading test on the sample, and recording experimental data; constructing an L-shaped laminated plate numerical model containing a cohesion unit, correcting the L-shaped laminated plate numerical model, and obtaining a key failure position according to the steps of the stress nephogram and the initial position of the crack; on the basis of the key failure position, the size and position of a prefabricated layering defect are designed; optimizing the L-shaped laminated plate numerical model to obtain an L-shaped laminated plate interlayer damage model with relatively high sensitivity to defect positions; and analyzing the influence of the layering defect position on the bearing capacity of the laminated plate and the failure model. The method for evaluating the damage tolerance of the composite material L-shaped plate containing the layering defect is low in cost, does not need to prepare a large number of defect samples, and is high in loading test efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of a comprehensive evaluation system for correcting numerical models with experimental data, and in particular to a damage tolerance evaluation method for a composite material L-shaped plate containing delamination defects. Background Art

[0002] Advanced fiber-reinforced resin-based composite materials are widely used in the aviation field due to their light weight and high strength. Their use in civil aircraft has become an important indicator of advancement. As a typical component of civil aircraft, L-shaped composite components are widely present in wing spars, wing ribs and long stringer structures, and are one of the most common connectors in composite aircraft. When subjected to bending loads, the bearing capacity of arc-shaped or large curvature sections (often called R zones), especially the R zones containing defects, is an important basis for determining the structural design value of L-shaped composite components. In the preparation process of L-shaped composite components, it is inevitable that defects such as delamination, wrinkles, resin enrichment, uneven thickness, fiber breakage and matrix cracking will occur in the R zone, which will reduce the bearing capacity of composite components to a certain extent. The damage tolerance design criteria for aviation composite materials stipulate that defects and damage are allowed in composite structures, but under the action of design loads, defects or damage cannot be extended.

[0003] There have been a large number of experimental and simulation studies on the failure modes and load-bearing capacity evaluation of L-shaped composite components, but there are few reports on the residual load-bearing capacity, failure modes and failure mechanisms of defective L-shaped composite components. These reports mainly involve three major defects: interlayer delamination, wrinkles and resin enrichment.

[0004] Wimmer was the first to use a research method that combines simulation and experiment to study the effect of delamination defect size on delamination growth. In terms of simulation, virtual crack closure technology (VCCT) was combined with implicit finite element analysis to simulate the growth process of delamination damage. The simulation results showed that for delamination defects of small size of 1mm, unstable delamination growth would occur, and when the delamination expanded to a certain size, it would turn into stable growth; for delamination defects of 3mm, the delamination growth under displacement load control was stable, while the delamination under force load control was unstable growth; and for delamination defects of 5mm, the delamination growth was always stable. In terms of experiments, thin film Teflon strips were buried in the pre-designed ply position to form delamination defects. The experimental results showed the same rules as the simulation.

[0005] after The work of

[14] introduced the cohesive force unit method proposed by Dugdale into the simulation of L-type laminates for the first time, which was used to simulate the interlaminar delamination occurring in the arc area of ​​the L-type laminates. Since then, the method of arranging cohesive force units between layers has been widely adopted to establish the interlaminar damage model of L-type laminates. The work of this paper is the first to dynamically analyze the delamination growth of L-shaped laminates. The results show that under the condition of lateral bending loading, the right crack tip grows mainly under shearing action, while the left crack tip grows mainly under opening action. The crack growth rate dominated by shear on one side is one order of magnitude faster than the crack growth rate dominated by opening on the other side. The experimental results are in good agreement with the simulation results.

[0006] Woo innovated the modeling method by incorporating the geometric shape characteristics of the defects contained in the specimen into the finite element mesh, and predicted the delamination development behavior through the finite element model. The load-displacement curve predicted by the model is more consistent with the experimental results than the model that does not consider the defect geometry, which verifies the accuracy of the proposed numerical modeling. The results show that in the absence of voids or when the size of the central defect is very small, the center of the interface 5 / 6 is the main location for delamination development. When the defect size increases, the center of the interface 6 / 7 and 7 / 8 is the main location for defect development. When the defect position moves toward the center of the R zone, the maximum load decreases. For the delamination defect at the same position, the larger the size, the smaller the maximum load.

[0007] Qian used manual laying and laid a 2mm wide and 0.16mm thick polyvinyl chloride film at the center of the corner, and designed three defect configurations: layered, stacked, and layered and stacked to simulate the defects caused by the lateral deviation of the fiber bundle during the automatic fiber placement (AFP) process. The results showed that the layered defect would significantly reduce the in-plane tensile strength ILTS (-31.2%).

[0008] At present, most of the research on delamination defects in the R zone of L-type laminates uses a combination of experiments and calculations. The conclusions show that the existence of delamination defects greatly reduces the interlaminar strength of L-type laminates and shows sensitivity to the defect location. These conclusions are one-sidedly pointing to the impact of defects at a certain point in the R zone on the L-type laminate. In fact, delamination defects may appear at any position in the R zone. In order to systematically study the impact of delamination defects on the bearing capacity of L-type composite laminates at all possible locations, a large number of defective specimens must be prepared and loaded for testing, which will undoubtedly consume a lot of manpower and financial resources. Summary of the invention

[0009] The purpose of the present invention is to provide a damage tolerance assessment method for an L-shaped composite plate containing a delamination defect, which has low cost, does not require the preparation of a large number of defective specimens, has high loading test efficiency, and can comprehensively study the bearing capacity of the L-shaped laminate composite material when the delamination defect is located at a certain position.

[0010] To achieve the above object, the present invention provides a method for evaluating the damage tolerance of a composite L-shaped plate containing delamination defects, comprising the following steps:

[0011] S1. Prepare defect-free L-shaped laminate specimens, perform loading tests on the specimens, and record stress distribution cloud diagrams, crack initiation positions at critical moments, and displacement load curves;

[0012] S2, construct a numerical model of an L-type laminate containing cohesive units, and use the data obtained in S1 to modify the numerical model of the L-type laminate, and obtain the key failure position according to the stress cloud map step by step and the crack initiation position;

[0013] S3. Design the size and location of prefabricated delamination defects based on the key failure location;

[0014] S4, further optimizing the numerical model of the L-type laminate according to the experimental results in S1, and obtaining an L-type laminate interlaminar damage model with high sensitivity to defect locations;

[0015] S5. Analyze the influence of delamination defect location on the bearing capacity and failure model of the laminate.

[0016] Preferably, the specific operation of S1 is: first prepare an L-shaped composite laminate by manual paving and autoclave molding, design and prefabricate three major types of delamination defects according to the stress distribution characteristics of the defect-free L-shaped composite laminate model: ply position, circumferential position, and defect size, and then perform four-point bending loading on the sample, use a high-speed camera to monitor the initiation and extension of delamination damage on the sample measuring surface, and record the load-displacement curve and stress distribution cloud map.

[0017] Preferably, the sample size in S1 is: the inner radius of the R zone is 6.4 mm, the right-angle loading arm is 90 mm, and the width is 25 mm.

[0018] Preferably, the numerical model of the L-type laminate in S2 is a finite element model with an inner radius of 6.4 mm, an outer radius of 10.72 mm, a thickness of 4.32 mm, a total of 24 layers, and a thickness of 0.18 mm for each layer. Considering the calculation accuracy and efficiency, the numerical model of the L-type laminate has a total of 177,968 nodes and 87,734 units, including 79,776 C3D8R units and 7,958 COH3D8 units. The grid is encrypted in the R zone, the loading arm transition zone, and the loading contact zone. For the boundary conditions in the simulation experiment, an analytical rigid cylinder is used. The loading rod is simulated, and the contact between the fixture and the specimen, as well as the interaction between the interfaces after failure, is simulated using frictionless surface contact conditions. The two rigid cylinders on the lower side are completely fixed, and the two rigid cylinders on the upper side are bound together with another rigid cylinder just above the corner through MPC multi-point constraints. A downward displacement load of 10 mm is applied, and constraints symmetrical about the plane perpendicular to the X-axis are applied to the laminate to completely limit its displacement in the Z and X directions. The laminate after equivalent calculation of prepreg parameters is used as the model material parameters to construct a numerical model of the L-type laminate.

[0019] Preferably, in S3, the experiment uses a method of embedding a polytetrafluoroethylene film to prefabricate the delamination defect, and the simulation model uses a method of deleting the cohesive force.

[0020] Preferably, in S5, the influence of the delamination defect position on the bearing capacity and failure mode of the L-type laminate is analyzed by arranging delamination defect envelope R zones that are evenly distributed and have the same size.

[0021] Therefore, the present invention adopts the above-mentioned damage tolerance assessment method for an L-shaped composite plate containing delamination defects, which has low cost, does not require the preparation of a large number of defective specimens, has high loading test efficiency, and can comprehensively study the bearing capacity of the L-shaped laminate composite material when the delamination defect is located at a certain position.

[0022] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the sample size of an embodiment of a damage tolerance assessment method for a composite material L-shaped plate containing delamination defects of the present invention;

[0024] Figure 2 It is a schematic diagram of prefabricated defect paving of an embodiment of a damage tolerance assessment method for a composite material L-shaped plate containing delamination defects of the present invention;

[0025] Figure 3 It is a curing process curve diagram of an embodiment of a damage tolerance assessment method for a composite material L-shaped plate containing delamination defects of the present invention;

[0026] Figure 4 It is a sample diagram of an L-shaped laminated plate according to an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention;

[0027] Figure 5 It is an assembly diagram of a numerical model of an L-shaped laminated plate according to an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention;

[0028] Figure 6 It is a mesh division diagram of a numerical model of an L-shaped laminated plate according to an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention;

[0029] Figure 7 It is a cohesive force unit position diagram of an embodiment of a damage tolerance assessment method for a composite L-shaped plate containing delamination defects of the present invention;

[0030] Figure 8 It is a triangle traction separation law TSL diagram of an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention;

[0031] Fig. 9 It is a radial stress distribution cloud diagram of a defect-free sample in an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention;

[0032] Fig.10 It is a representative defect point map of an embodiment of a damage tolerance assessment method for a composite L-shaped plate containing delamination defects of the present invention;

[0033] Fig.11 It is a defect lattice envelope diagram of an embodiment of a damage tolerance assessment method for a composite material L-shaped plate containing delamination defects of the present invention;

[0034] Fig.12 It is a force displacement curve comparison diagram of an embodiment of a damage tolerance assessment method for a composite material L-shaped plate containing delamination defects of the present invention;

[0035] Fig.13 It is a comparison diagram of a force-displacement curve of a prefabricated delamination specimen of an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects and a simulation result containing delamination defects;

[0036] Fig.14 It is a defect position-limit load surface diagram of an embodiment of a damage tolerance assessment method for an L-shaped composite material plate containing delamination defects of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0038] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0039] The present invention provides a damage tolerance assessment method for a composite L-shaped plate containing delamination defects, comprising the following steps:

[0040] S1. Prepare defect-free L-type laminate specimens, conduct loading tests on the specimens, and record stress distribution cloud maps, crack initiation positions at critical moments, and displacement load curves. The specific operations are as follows: first, prepare L-type composite laminates by manual paving and autoclave molding. According to the stress distribution characteristics of the defect-free L-type composite laminate model, design and prefabricate three major types of delamination defects: ply position, circumferential position, and defect size. Then, perform four-point bending loading on the specimens, use a high-speed camera to monitor the initiation and extension of delamination damage on the specimen measuring surface, and record the load-displacement curve and stress distribution cloud map. The specimen dimensions are as follows: the inner radius of the R zone is 6.4 mm, the right-angle loading arm is 90 mm, and the width is 25 mm.

[0041] S2, construct a numerical model of an L-type laminate containing cohesive units, and use the data obtained in S1 to modify the numerical model of the L-type laminate, and obtain the key failure position according to the stress cloud map step by step and the crack initiation position;

[0042] The numerical model of the L-type laminate is a finite element model with an inner radius of 6.4 mm, an outer radius of 10.72 mm, a thickness of 4.32 mm, a total of 24 layers, and a thickness of 0.18 mm for each layer. In terms of comprehensive calculation accuracy and efficiency, the numerical model of the L-type laminate has a total of 177,968 nodes and 87,734 units, including 79,776 C3D8R units and 7,958 COH3D8 units. The grid is encrypted in the R zone, the transition zone of the loading arm, and the loading contact zone. For the boundary conditions in the simulation experiment, an analytical rigid cylinder is used to simulate the loading. The rod is loaded, and the frictionless surface contact condition is used to simulate the contact between the fixture and the specimen, as well as the interaction between the interfaces after failure. The two rigid cylinders on the lower side are completely fixed, and the two rigid cylinders on the upper side are bound together with another rigid cylinder just above the corner through MPC multi-point constraints. A downward displacement load of 10 mm is applied, and the laminate is constrained symmetrically about the plane perpendicular to the X-axis to completely limit its displacement in the Z and X directions. The laminate after equivalent calculation of prepreg parameters is used as the model material parameters to construct a numerical model of the L-type laminate.

[0043] S3. Based on the critical failure position, the size and position of the prefabricated delamination defect are designed. In the experiment, the delamination defect is prefabricated by burying polytetrafluoroethylene film, and the cohesive force is deleted in the simulation model.

[0044] S4, further optimizing the numerical model of the L-type laminate according to the experimental results in S1, and obtaining an L-type laminate interlaminar damage model with high sensitivity to defect locations;

[0045] S5. The influence of the delamination defect position on the bearing capacity and failure model of the laminate is analyzed by arranging delamination defect envelope R zones with uniform distribution and the same size.

[0046] Embodiment 1

[0047] The present invention provides a damage tolerance assessment method for a composite L-shaped plate containing delamination defects, comprising the following steps:

[0048] S1. Prepare defect-free L-shaped laminate specimens, conduct loading tests on the specimens, and record stress distribution cloud maps, crack initiation positions at critical moments, and displacement load curves. The specific operations are as follows: first, prepare L-shaped composite laminates by manual paving and autoclave molding. According to the stress distribution characteristics of the defect-free L-shaped composite laminate model, design and prefabricate three major types of delamination defects: ply position, circumferential position, and defect size. Then, perform four-point bending loading on the specimens, use a high-speed camera to monitor the initiation and extension of delamination damage on the specimen measuring surface, and record the load-displacement curve and stress distribution cloud map.

[0049] The sample dimensions are as follows: the inner radius of the R zone is 6.4 mm, the right-angle loading arm is 90 mm, and the width is 25 mm. The raw material of the sample is T700-grade carbon fiber prepreg provided by Jiangsu Hengshen Co., Ltd., model EV201-35%-12KHF10-U-200gsm-1000, resin content is 35±3%, and fiber surface density is 200±10%. The material parameters provided by the prepreg manufacturer are shown in Table 1, and the main experimental instruments used in the preparation of the sample and experimental testing are shown in Table 2.

[0050] Table 1 Prepreg material parameters

[0051] Material properties Numeric <![CDATA[E 11 / GPa]]> 126 <![CDATA[E 22 / GPa]]> 11 <![CDATA[E 33 / GPa]]> 11 <![CDATA[μ 12 ]]> 0.29 <![CDATA[μ 13 ]]> 0.29 <![CDATA[μ 23 ]]> 0.40 <![CDATA[G 12 / GPa]]> 6.6 <![CDATA[G 13 / GPa]]> 6.6 <![CDATA[G 23 / GPa]]> 3.9

[0052] Table 2 Main experimental instruments used in sample preparation and experimental testing

[0053] Experimental instruments Manufacturer Device Model Autoclave Lontek RG-21 Vacuum Pump Zhejiang Qiujing Technology 2XZ-2 Cutting Machine BOSUN ZIE(T)-350Ae(b) Angle grinder BOSUN BS-2 Belt Grinder Suzhou Tianyiwei Electric HBS78B Micro-CT BRUKER Skyscan-1273 Electronic universal testing machine MTS MTS370 SLR camera Nikon D90 High-speed camera Zhongzheng Instruments ZZLJ-2000H

[0054] The sample was prepared by manual paving method. The paving scheme for defect-free samples was [0] 24 , where 0° is along the outer curvature direction, the specimen has 24 layers, and the thickness after curing is 4.32 mm. The main operating steps for manually laying specimens include: cutting prepreg, mold pretreatment, laying prepreg, and vacuum pre-compacting. In order to reduce bubbles and bulging during laying, vacuum pre-compacting is performed every 6 layers of prepreg. An L-shaped composite laminate with delamination defects is prepared by laying polytetrafluoroethylene film on the prepreg. The production process is as follows: When laying the laminate, when the number of prepreg layers reaches the number of layers that need to prefabricate defects, use a paper cutter to cut the polytetrafluoroethylene into strips of preset width, lay it flat on the curved part of the L-shaped specimen, and confirm the position of the defect by the scale pre-marked on the mold, such as Figure 2 As shown, the mold used to prepare the specimen is an L-shaped Invar female mold with an inner chamfer radius of 10.72 mm.

[0055] The hand-laid prepreg is cured by the autoclave molding process. The curing process curve used by the autoclave is as follows: Figure 3 As shown, Figure 3(a) is the curing temperature curve. Figure 3 (b) is the curing pressure curve. After the process curve in the autoclave is completed, the mold is taken out and demoulding can be performed after a period of cooling. After the laminate motherboard is cured and formed, the cutting machine is used to cut off the scraps. Six identical samples can be cut from a prepared motherboard. The actual sample of the L-shaped laminate is shown in the figure. Figure 4 shown.

[0056] S2. Construct a numerical model of an L-type laminate containing cohesive units, and use the data obtained in S1 to modify the numerical model of the L-type laminate. The critical failure position is obtained according to the stress cloud map step by step and the crack initiation position.

[0057] The numerical model of the L-type laminate is a finite element model. The model assembly diagram is shown in Figure 5 The model mesh is divided as shown in Figure 6 As shown in the figure, the model has an inner radius of 6.4 mm, an outer radius of 10.72 mm, a thickness of 4.32 mm, a total of 24 layers, and each layer is 0.18 mm thick. In terms of calculation accuracy and efficiency, the numerical model of the L-type laminate has a total of 177,968 nodes and 87,734 units, including 79,776 C3D8R units and 7,958 COH3D8 units. The grid is encrypted in the R zone, the transition zone of the loading arm, and the loading contact zone. To simulate the boundary conditions in the experiment, an analytical rigid cylinder is used to simulate the loading rod, and an unstructured grid is used. The surface-to-surface contact condition of friction simulates the contact between the fixture and the specimen, as well as the interaction between the interfaces after failure. The two rigid cylinders on the lower side are completely fixed, and the two rigid cylinders on the upper side are bound together with another rigid cylinder just above the corner through MPC multi-point constraints. A downward displacement load of 10 mm is applied, and constraints symmetrical about the plane perpendicular to the X-axis are applied to the laminate to completely restrict its displacement in the Z and X directions. The laminate after equivalent calculation of prepreg parameters is used as the model material parameters to construct a numerical model of the L-type laminate.

[0058] In order to ensure the reproducibility of the simulation experiment to the greatest extent, the laminate parameters calculated equivalently to the prepreg parameters are used as the model material parameters, among which the radial tensile strength is measured by the DCB experiment. Table 3 shows the relevant parameters.

[0059] Table 3 Equivalent laminate parameters

[0060] Material parameters Numeric <![CDATA[E 11 / GPa]]> 126 <![CDATA[E 22 / GPa]]> 11 <![CDATA[E 33 / GPa]]> 11 <![CDATA[μ 12 ]]> 0.29 <![CDATA[μ 13 ]]> 0.29 <![CDATA[μ 23 ]]> 0.40 <![CDATA[X t / MPa]]> 1950 <![CDATA[X c / MPa]]> 1480 <![CDATA[Y t / MPa]]> 48

[0061] Zero-thickness cohesive elements are arranged between the layers in the arc region of the L-shaped composite material to simulate the delamination damage between the layers. Figure 7 , a PYTHON-based parametric modeling method is used to assist in improving modeling efficiency and reducing the probability of manual modeling errors.

[0062] Cohesive zone elements (CZM) are a finite element modeling technique that simulates material damage by exploiting crack propagation caused by gradual separation of material interfaces. Discontinuities in the material are modeled using a special type of viscous finite element, where zero-thickness cohesive zones are inserted between regular volume finite elements. Cohesive zones should be inserted where delamination is likely to occur, i.e. between each layer of the laminate, e.g. Figure 7 shown.

[0063] During loading, the mechanical behavior of the laminate elements remains elastic-plastic. However, the cohesive elements between the laminate elements have unique mechanical behavior defined by a specific traction separation law (TSL). When the conditions set by the traction separation law are met, these zero-thickness cohesive elements represent the discontinuity of the structure by acquiring a finite volume.

[0064] Once the deformation exceeds the limit of the traction-separation law, the cohesive unit no longer transmits any force, which is essentially equivalent to a void space. Several traction-separation law models have been proposed by different researchers, including exponential, cubic polynomial, trapezoidal, triangular, linear and polynomial softening, and hardening-softening.

[0065] Triangle TSL Figure 8 As shown in Figure 2, the traction separation law is given by the maximum interface traction force (T max ), cohesive stiffness (K eff ), initial destruction separation (δ0), final destruction separation (δ f ) and fracture energy (G C ). The maximum traction is the traction that the cohesive element bears before cracking occurs. The initial slope is the effective cohesive stiffness (K eff ). The fracture energy, or area under the curve, is defined as the energy consumed by the creation of a new crack surface. The initial and final failure displacements determine the initiation and propagation of fracture, respectively.

[0066] Through the double cantilever beam test (DCB), all the above parameters can be obtained directly or indirectly, and the maximum interface traction T max The value of T will have a certain impact on the prediction results. max The value of will affect the accuracy and convergence of the calculation results.

[0067] Another important parameter to determine is the cohesive stiffness, which can have a significant impact on the overall elastic response if the number of cohesive elements is large or the thickness is limited, i.e., the additive compliance effect. Since the cohesive elements only need to simulate fracture, their impact on the overall stiffness should be minimized.

[0068] When the number of cohesive elements inserted in the model is large and the cohesive elements are inserted in multiple layers, K effThe value of becomes particularly important. In order to minimize the effect of the additional flexibility, K is set relative to the stiffness of the laminate element. eff It should be as large as possible, however, if the value is too large, it may increase the numerical error and cause problems in the convergence of the solution, so a series of preliminary analyses are performed and the cohesive stiffness value is selected that is close in value to the elastic response compared to the laminate element.

[0069] S3. Based on the critical failure position, the size and position of the prefabricated delamination defect are designed. In the experiment, the delamination defect is prefabricated by burying polytetrafluoroethylene film, and the cohesive force is deleted in the simulation model.

[0070] S4. Based on the experimental results in S1, the numerical model of the L-type laminate is further optimized to obtain an L-type laminate interlaminar damage model with high sensitivity to defect locations.

[0071] First, according to Fig. 9 The radial stress distribution cloud diagram of the defect-free model shown in the figure sets six representative defect points with a defect size of 2 mm. Fig.10 shown.

[0072] Then, the results are compared with the loading test results of the defective specimen to verify the sensitivity of the numerical model to the defect location. The model is further modified to make it more sensitive to the defect location, thereby increasing the credibility of the defect lattice envelope simulation results in the next step.

[0073] S5. The influence of the delamination defect position on the bearing capacity and failure model of the laminate is analyzed by arranging delamination defect envelope R zones with uniform distribution and the same size.

[0074] In order to more comprehensively and systematically study the effect of defects at different positions on the bearing capacity of L-type laminates, 96 defect points with uniform distribution and size are set to envelop the entire R region, such as Fig.11 shown.

[0075] The force displacement curve collected by the loading platform and the force displacement curve obtained by simulation are shown in Fig.12 As shown in the figure, the elastic response of the model is basically consistent with that of the sample, and the curves are well matched. The model has initially acquired the ability to predict the delamination behavior of defect-free samples.

[0076] The force displacement curve of the prefabricated delaminated specimen collected by the loading platform and the simulation results with delaminated defects are shown in Figure 2. Fig.13 As shown in the figure, the maximum load of the characteristic point defect specimen predicted by the model has a small error with the experimental results, and the degree of agreement is above 97%. The model is highly sensitive to the defect location.

[0077] After comparing the defect position simulation with the experiment, it is shown that the model is highly sensitive to the defect position. The limit load corresponding to each defect point on the envelope surface is extracted and plotted into a scatter plot with the plane absolute coordinates of the defect point. The normalized plot is then processed into a defect position-limit load surface diagram, as shown in Figure 2. Fig.14 shown.

[0078] The results show that when defects of the same size appear in different locations, the ultimate bearing capacity differs by about 37%. The closer the defect location is to 45° of the 9th and 10th floors, the lower the ultimate load. In a relatively long high-risk area (10-35°) between the 9th and 10th floors, if defects occur, the ultimate load will drop by about one third.

[0079] Therefore, the present invention adopts the above-mentioned damage tolerance assessment method for an L-shaped composite plate containing delamination defects, which has low cost, does not require the preparation of a large number of defective specimens, has high loading test efficiency, and can comprehensively study the bearing capacity of the L-shaped laminate composite material when the delamination defect is located at a certain position.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A damage tolerance assessment method for a composite L-shaped plate containing delamination defects, characterized in that: The following steps are involved: S1. Prepare defect-free L-shaped laminate specimens, perform loading tests on the specimens, and record stress distribution cloud diagrams, crack initiation positions at critical moments, and displacement load curves; S2, construct a numerical model of an L-type laminate containing cohesive units, and use the data obtained in S1 to modify the numerical model of the L-type laminate, and obtain the key failure position according to the stress cloud map step by step and the crack initiation position; S3. Design the size and location of prefabricated delamination defects based on the key failure location; S4, further optimizing the numerical model of the L-type laminate according to the experimental results in S1, and obtaining an L-type laminate interlaminar damage model with high sensitivity to defect locations; S5. Analyze the influence of delamination defect location on the bearing capacity and failure model of the laminate.

2. The damage tolerance assessment method for a composite L-shaped plate containing delamination defects according to claim 1, characterized in that: The specific operation of S1 is as follows: first, prepare the L-shaped composite laminate by manual paving and autoclave molding; according to the stress distribution characteristics of the defect-free L-shaped composite laminate model, design and prefabricate three major types of delamination defects: ply position, circumferential position, and defect size; then, perform four-point bending loading on the specimen; use a high-speed camera to monitor the initiation and extension of delamination damage on the specimen measuring surface; and record the load-displacement curve and stress distribution cloud map.

3. The damage tolerance assessment method for a composite L-shaped plate containing delamination defects according to claim 1, characterized in that: The specimen dimensions in S1 are: the inner radius of the R zone is 6.4 mm, the right-angle loading arm is 90 mm, and the width is 25 mm.

4. The damage tolerance assessment method for a composite L-shaped plate containing delamination defects according to claim 1, characterized in that: The numerical model of the L-type laminate in S2 is a finite element model with an inner radius of 6.4 mm, an outer radius of 10.72 mm, a thickness of 4.32 mm, a total of 24 layers, and a thickness of 0.18 mm for each layer. Considering the calculation accuracy and efficiency, the numerical model of the L-type laminate has a total of 177,968 nodes and 87,734 units, including 79,776 C3D8R units and 7,958 COH3D8 units. The grid is encrypted in the R zone, the loading arm transition zone, and the loading contact zone. For the boundary conditions in the simulation experiment, an analytical rigid cylinder simulation is used. The loading rod uses frictionless surface contact conditions to simulate the contact between the fixture and the specimen, as well as the interaction between the interfaces after failure. The two rigid cylinders on the lower side are completely fixed, and the two rigid cylinders on the upper side are bound together with another rigid cylinder just above the corner through MPC multi-point constraints. A downward displacement load of 10 mm is applied, and constraints symmetrical about the plane perpendicular to the X-axis are applied to the laminate to completely limit its displacement in the Z and X directions. The laminate after equivalent calculation of prepreg parameters is used as the model material parameters to construct a numerical model of the L-type laminate.

5. The damage tolerance assessment method for a composite L-shaped plate containing delamination defects according to claim 1, characterized in that: In the experiment of S3, the delamination defect was prefabricated by burying polytetrafluoroethylene film, and the cohesive force was deleted in the simulation model.

6. The damage tolerance assessment method for a composite L-shaped plate containing delamination defects according to claim 1, characterized in that: In S5, the influence of the delamination defect position on the bearing capacity and failure mode of the L-type laminate is analyzed by arranging the delamination defect envelope R zone with uniform distribution and the same size.

Citation Information

Patent Citations

  • Delamination propagation behavior simulation method of composite material multidirectional laminated plate on basis of cohesion model

    CN103605865A

  • Finite element analysis method of residual strength of laminated board containing layered composite material

    CN106354965A

  • CFRP laminate delamination failure behavior prediction method based on novel cohesion constitutive relation

    CN110376055A

  • Accurate prediction method for layered damage and mechanical behaviors of perforated composite laminated plate

    CN110909498A

  • Damage tolerance characterization method for laminated plate containing layered damage by taking layered area as evaluation index

    CN111310364A